2018
DOI: 10.1002/jper.17-0062
|View full text |Cite
|
Sign up to set email alerts
|

Mean annual attachment, bone level, and tooth loss: A systematic review

Abstract: Background: Rate of progression of periodontitis has been used to inform the design

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 67 publications
2
54
0
5
Order By: Relevance
“…Similarly, our study, which included both sexes and non‐menopausal women, reported a mean CAL difference of 0.3 mm between the osteoporosis and normal BMD groups. According to a systematic review and meta‐analysis of prospective studies on periodontitis progression, the average mean CAL loss was 0.1 mm/year . Therefore, the mean CAL difference of 0.3 mm reported in the previous systemic review and in our study is clinically relevant.…”
Section: Discussionsupporting
confidence: 66%
“…Similarly, our study, which included both sexes and non‐menopausal women, reported a mean CAL difference of 0.3 mm between the osteoporosis and normal BMD groups. According to a systematic review and meta‐analysis of prospective studies on periodontitis progression, the average mean CAL loss was 0.1 mm/year . Therefore, the mean CAL difference of 0.3 mm reported in the previous systemic review and in our study is clinically relevant.…”
Section: Discussionsupporting
confidence: 66%
“…The beneficial effect of periodontal care was then reported, with a mortality between 0.11 and 0.24 t/y after both surgery and supportive therapy, and between 0.22 and 0.29 t/y in case of treatment not followed by supportive care (Becker, Becker, et al, ; Becker Berg, & Becker, , ; Tonetti, Muller‐Campanile, & Lang, ). A systematic review part of the 2017 World Workshop reported that annual tooth loss increases with advancing age and does not differ when comparing geographic groups (Needleman et al, ). In the same review, counting a pool of over 8,600 patients without periodontal intervention, the mean rate of t/y was 0.2 with no gender differences.…”
Section: Long‐term Tooth Retention What Would Be An Acceptable Rate mentioning
confidence: 99%
“…Furthermore, a thorough evaluation of the scientific evidence conducted as part of the due diligence process in preparation of the classification workshop did not support the existence of different forms of periodontitis based on clear differences in pathobiology (Papapanou et al, ). At present, there is neither adequate knowledge of unique mechanisms nor evidence to support the need for specific treatments to justify the distinction between aggressive and chronic periodontitis (Fine, Patil, & Loos, ; Lang et al, ; Lindhe et al, ; Needleman et al, ; Tonetti et al, ).…”
Section: Introductionmentioning
confidence: 99%